Hiperealitas dalam Iklan Rokok Dji Sam Soe dan Gudang Garam - Tristan Alfian; Dwi Retna Sulistyawati (SULUH: Jurnal Seni Desain Budaya, 2018)
An advertisement implies deviation and hidden of certain reality then it leads consumer to hyperreality world. In a context of tobacco advertising, it emphasizes more about image and impression, so consumers are not aware of a risk. The result shows that tobacco advertising constitutes reality discourse which is hyperreality. It is a discourse about image reality in tobacco advertising which describes, stimulates, and project of a dream world of hyperreality. The imagery in cigarette advertisements of Dji Sam Soe and Gudang Garam cannot be separated from aesthetic creativity that conveys confusion of bookmarks, styles, and phrases in cigarette advertisement work.